UPAYA PENINGKATAN KARAKTER AGAMA DAN MORAL ANAK USIA DINI DENGAN METODE BERCERITA PADA KELOMPOK B3 DI TK MASYITOH WELAHAN WETAN TAHUN AJARAN 2022/2023 - Wahda Qurrota Aini; Sandi Aji Wahyu Utomo (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2023)
This study aims to find out how effective the storytelling method is in increasing the religious and moral character of Masyithoh Kindergarten students, class B3, even semester. Therefore, it is subject to action by carrying out learning using the storytelling method to 29 students, to find out the changes that occur in the religious and moral character of students. This research is a class action research with all 29 students in class B3 TK Masyithoh Welahan Wetan as subjects. This research instrument uses observation, interviews, and documentation. Data analysis was carried out using a qualitative descriptive method, but also supported by quantitative data. Qualitative data analysis is accomplished by several steps, including: data collection, data reduction, data display and drawing conclusions. Meanwhile, quantitative data analysis was taken by calculating the percentage results of action observations. The results of the study showed that learning using the storytelling method could improve the religious and moral character of B3 class students of Mayithoh Welahan Wetan Kindergarten. In cycle I, the percentage of students' religious and moral character improvement was 62%, in cycle II, the percentage increased to 78%. This shows an increase in the religious and moral character of students after being subjected to action using the storytelling method. Based on the results of student mastery in cycle II of 78%, then in terms of achieving the goals set, namely 75%, the application of the storytelling method in improving the religious and moral character of class B3 TK Masyithoh Welahan Wetan can be said to be successful with the good category, then storytelling as the learning method in this study met the criteria of effectiveness with a percentage of 78%.